Pain sensation in human osteoarthritic knee joints is strongly enhanced by diabetes mellitus. Issue 9 (September 2017) - Eitner, Annett; Pester, Julia; Vogel, Franziska; Marintschev, Ivan; Lehmann, Thomas; Hofmann, Gunther O.; Schaible, Hans-Georg
Abstract : Abstract: The major burden of knee joint osteoarthritis (OA) is pain. Since in elder patients diabetes mellitus is an important comorbidity of OA, we explored whether the presence of diabetes mellitus has a significant influence on pain intensity at the end stage of knee OA, and we aimed to identify factors possibly related to changes of pain intensity in diabetic patients. In 23 diabetic and 47 nondiabetic patients with OA undergoing total knee arthroplasty, we assessed the pain intensity before the operation using the "Knee Injury and Osteoarthritis Outcome Score". Furthermore, synovial tissue, synovial fluid (SF), cartilage, and blood were obtained. We determined the synovitis score, the concentrations of prostaglandin E2 and interleukin-6 (IL-6) in the SF and serum, and of C-reactive protein and HbA1c and other metabolic parameters in the serum. We performed multivariate regression analyses to study the association of pain with several parameters. Diabetic patients had on average a higher Knee Injury and Osteoarthritis Outcome Score pain score than nondiabetic patients ( P < 0.001). Knee joints from diabetic patients exhibited on average higher synovitis scores ( P = 0.024) and higher concentrations of IL-6 in the SF ( P = 0.003) than knee joints from nondiabetic patients. Multivariate regression analysis showed that patients with higher synovitis scores had more intense pain independent of all investigated confounders, and that the positive association between pain intensities and IL-6 levels was dependent on diabetes mellitus and/or synovitis. These data suggest that diabetes mellitus significantly increases pain intensity of knee OA, and that in diabetic patients higher pain intensities were determined by stronger synovitis. Abstract : Diabetes mellitus is an important comorbidity of osteoarthritis which aggravates osteoarthritis pain intensity. Factors involved are high synovitis scores and high intraarticular interleukin-6 concentrations.